Experiencing vulnerability in southern Africa: The interaction of multiple stressors - Casale, Marisa; Drimie, Scott; Gillespie, Stuart; Kadiyala, Suneetha; Msoma, Paul; Quinlan, Tim; Ziervogel, Gina (International Food Policy Research Institute, 2008)
The word “vulnerability” is often used by development agencies and scientists when speaking about human welfare in Southern Africa. It is known that increasing poverty, AIDS, and food insecurity are some of the threats that make households more “vulnerable” to different shocks and stressors But what does vulnerability really mean for a household in peri-urban South African townships, a family in Chikamba, a rural village in Malawi, or migrant workers in Durban? And how can it be used effectively in development work? These are some of the key questions that have driven this research.